The Bibliotecology and its social projection - Gil Calderón, Marcela (2011)
An exploratory study whose general objective was to conduct an assessment of the situation of access to bibliographic information on Costa Rica, by the following user groups: the disabled, prisoners, the elderly and long-stay inpatients; during the period between 2006-2008. Both for the collection and to data analysis, was used as base the technical guidelines developed by the Library Services for people with special needs of the International Federation of Library Associations and Institutions, known by its acronym in English as IFLA. The diagnostic results indicate that access to bibliographic information is being provided to some extent to people with disabilities and older adults, while the detainees and long-stay hospitalized persons are deprived of these services.